ESKALASI DAN FORCE MAJEUR DALAM PERUNDANG - UNDANGAN JASA KONSTRUKSI - Herman Brahmana; Bismar Nasution; Suhaidi Suhaidi; Mahmul Siregar (USU LAW JOURNAL, 2015)
ABSTRACT Escalation is a legal instrument for the contractor to submit a price adjustment in terms of increasing the cost of implementing the value of the work to the value of the work at the time the contract was agreed to form a multi-year contract unit price. In its application the government through a joint decision of the Minister of Finance and the Minister of Public Works in 2008 and in 2013, imposes an escalation of all the projects that will be or are in the stages of processing due to rising prices of raw materials kontsruksi as the impact of rising fuel. Legislation construction services do not define the limits and the escalation of force majeure. Restrictions state is necessary as a handle to gain a complete understanding of the escalation and force majeure. From these results it can be seen escalation may be filed if the service providers comply with the limits that state, the rising cost of execution of work, increasing the cost of implementing such work can not be predicted by the service provider when the contract was agreed, bound service providers complete the work, and service providers are able to complete work, while the force majeure may be submitted by service providers if they meet the restrictions that state, the incident involuntary service providers, events beyond the ability of service providers to complete the work, due to the events that led to losses for service users. Keywords: escalation, force majeure, construction services.